Exploring the associations and potential mediators between lipid biomarkers and the risk of developing gout: NHANES 2007–2018 - Yuzhe Huang; Ying Li; Zhounan Wu; Yuhang Liang; Jinshen He (Lipids in Health and Disease)
Abstract Background Gout stands as a prevailing manifestation of inflammatory arthritis. While it is linked to several well-established risk factors, the associations between lipid profiles and the risk of gout remain unclear. Methods This research involved National Health and Nutrition Examination Survey data (2007–2018). The cardiometabolic index, which incorporates the Triglycerides (TG)/High-density lipoprotein cholesterol (HDL) ratio and waist to height ratio (WHtR), was used to assess lipid profiles and metabolic health. Multivariate logistic regression analysis, propensity score matching, and mediation analyses were utilized to evaluate the associations of lipid profiles and the cardiometabolic index with the risk of developing gout. Results Among 11,032 participants, each 1-unit increase in TG levels was associated with a 65% increase in the odds of developing gout before matching [1.65 (1.15–2.38), P = 0.007] and a 155% increase in the odds of developing gout after matching [2.55 (1.59–4.09), P = 0.007]. Each 1-unit increase in the cardiometabolic index was linked to an 81% increase in the odds of developing gout before matching [1.81 (1.22–2.70), P = 0.004] and a 215% increase in the odds of developing gout after matching [3.15 (1.84–5.40), P < 0.001]. The participants with HDL levels in the third quartile presented a 35% reduction in gout risk relative to those with HDL levels in the first quartile before matching [0.65 (0.46–0.92), P = 0.014] and a 51% reduction in gout risk after matching [0.49 (0.32–0.75), P < 0.001]. Mediation analyses revealed that BMI, WHtR, and homeostatic model assessment for insulin resistance (HOMA-IR) mediated the relationships between TG levels and the risk of developing gout at 18.75%, 24.28%, and 5.35%, respectively. For the association between HDL levels and the risk of developing gout, the mediating effects of BMI, WHtR, leukocytes, γ-glutamyltransferase (in those with HDL < 56 mmol/L), and HOMA-IR were 57.98%, 69.03%, 8.77%, 5.18%, and 11.14%, respectively. Conclusion This study reveals the relationship between lipid profiles and the risk of developing gout. Regularly checking TG and HDL levels and actively managing obesity, insulin resistance, oxidative stress and inflammation are important for lowering the risk of developing gout.